Poorly Expressed Alleles of Several Human Immunoglobulin Heavy Chain Variable Genes are Common in the Human Population - Ohlin, Mats (Frontiers in Immunology, 2021)
Extensive diversity has been identified in the human heavy chain immunoglobulin locus, including allelic variation, gene duplication, and insertion/deletion events. Several genes have been suggested to be deleted in many haplotypes. Such findings have commonly been based on inference of the germline repertoire from data sets covering antibody heavy chain encoding transcripts. The inference process operates under conditions that may limit identification of genes transcribed at low levels. The presence of rare transcripts that would indicate the existence of poorly expressed alleles in haplotypes that otherwise appear to have deleted these genes has been assessed in the present study. Alleles IGHV1-2*05, IGHV1-3*02, IGHV4-4*01, and IGHV7-4-1*01 were all identified as being expressed from multiple haplotypes, but only at low levels, haplotypes that by inference often appeared not to express these genes at all. These genes are thus not as commonly deleted as previously thought. An assessment of the 5’ untranslated region (up to and including the TATA-box), the signal peptide-encoding part of the gene, and the 3’-heptamer suggests that the alleles have no or minimal sequence difference in these regions in comparison to highly expressed alleles. This suggest that they may be able to participate in immunoglobulin gene rearrangement, transcription and translation. However, all four poorly expressed alleles harbor unusual sequence variants within their coding region that may compromise the functionality of the encoded products, thereby limiting their incorporation into the immunoglobulin repertoire. Transcripts based on IGHV7-4-1*01 that had undergone somatic hypermutation and class switch had mutated the codon that encoded the unusual residue in framework region 3 (cysteine 92; located far from the antigen binding site). This finding further supports the poor compatibility of this unusual residue in a fully functional protein product. Indications of a linkage disequilibrium were identified as IGHV1-2*05 and IGHV4-4*01 co-localized to the same haplotypes. Furthermore, transcripts of two of the poorly expressed alleles (IGHV1-3*02 and IGHV4-4*01) mostly do not encode in-frame, functional products, suggesting that these alleles might be essentially non-functional. It is proposed that the functionality status of immunoglobulin genes should also include assessment of their ability to encode functional protein products.